Effect of Insulin Resistance on Prognosis of Intravenous Thrombolysis in Acute Ischemic Stroke Patients with or Without Type 2 Diabetes Mellitus - Sun Y; Deng W; Luo L; Chen M (Diabetes, Metabolic Syndrome and Obesity)
Yanli Sun,1,2 Wei Deng,3 Li Luo,1 Mingwei Chen1 1Department of Endocrinology, The First Affiliated Hospital of Anhui Medical University, Hefei City, Anhui Province, People’s Republic of China; 2Department of General Practice, Xiangyang No.1 People’s Hospital, Hubei University of Medicine, Xiangyang City, Hubei Province, People’s Republic of China; 3Department of Neurology, Xiangyang No.1 People’s Hospital, Hubei University of Medicine, Xiangyang City, Hubei Province, People’s Republic of ChinaCorrespondence: Mingwei Chen; Li Luo, Department of Endocrinology, The First Affiliated Hospital of Anhui Medical University, No. 218 Jixi Road, Shushan District, Hefei City, Anhui Province, People’s Republic of China, Tel +86-551-2923631, +86-551-2926292, Email chmw1@163.com; 89200398@qq.comIntroduction: This study aims to investigate the significance of insulin resistance (IR) markers in predicting 48-hour hemorrhagic transformation and 3-month poor prognosis in acute ischemic stroke (AIS) patients of intravenous thrombolysis (IVT), with or without type 2 diabetes mellitus (T2DM).Methods: A total of 1352 patients with AIS treated with IVT between January 2019 and December 2023 were retrospectively reviewed. We analyzed the prognostic value of IR markers, including the triglyceride-glucose (TyG) index, triglyceride and body mass index (TYG-BMI), and the insulin resistance metabolic score (METS-IR), in AIS patients who received IVT with or without T2DM. The primary outcome was 48-hour hemorrhagic transformation and 3-month poor prognosis (modified Rankin Scale [mRS] ≥ 3).Results: Among 1181 enrolled patients, 328 were diagnosed with T2DM, representing 27.8% of the cohort. T2DM group showed a higher proportion of poor prognosis (23% vs.11%, p < 0.001), but no significant difference in hemorrhagic transformation between the two groups. TyG index, TyG-BMI, and METS-IR all demonstrated predictive value for 3-month poor prognosis, with the TyG index showing the highest predictive accuracy [area under the curve (AUC): 0.848]. The optimal cutoff point for predicting poor prognosis was 7.409, with sensitivity of 0.762 and specificity of 0.855 (p < 0.001). However, all three indexes were limited in their ability to predict hemorrhagic transformation.Conclusion: Elevated TyG index is an independent risk factor for 3-month poor prognosis in AIS patients of IVT with or without type T2DM, with the TyG index showing the highest predictive value. These findings provide a new understanding that IR can be used as a therapeutic target for AIS patients of IVT.Keywords: TyG index, TYG-BMI, METS-IR, hemorrhagic transformation, poor prognosis